Development of approaches to improving organization structure and staff composition of construction companies in terms of costs - Jawed Serat (Вестник СибАДИ, 2025)
Introduction. Under modern conditions construction companies have to be highly flexible and able to quickly adapt their organization structure and personnel to the requirements of each project. To achieve maximum effect in completing construction tasks, it is important to improve organization structure and staff composition taking into account costs. Given the specifics of construction work, high technical complexity of objects and the need to meet strict deadlines, approaches to organizing management processes should take into account both technological and qualification factors, and the costs of allocating labor resources.This article discusses methods for improving organization structure of construction companies with an emphasis put on increasing efficiency while meeting deadlines.Materials and methods. The study uses methods of system analysis to assess the current efficiency of the organization structure of construction companies. To identify ways to improve the staff structure and distribute tasks among employees, mathematical models based on cost and productivity analysis were used.The analysis of factors affecting the operational staff structure included employee qualifications, specifics of construction work and their technological features. Considerable attention has been paid to the costs on training and advanced training of employees, taking into account the requirements of various types of construction projects.Scientific novelty. The paper proposes new approaches to improving organization structure of construction companies aimed at redistributing tasks and functions among employees taking into account the specifics of projects. The developed model allows to optimize staff composition, provide capability of the organization structure to respond promptly to changes in the construction process. Evaluation of costs and productivity at each stage of construction works helps to increase the reliability and efficiency of project implementation.Results. The conducted research has shown that improvement of the organization structure and staff composition of construction companies requires application of an integrated approach to the redistribution of labor resources. This includes an emphasis on improving the qualifications of personnel, clarifying functions distribution and improving interaction between departments. Optimization of personnel costs, taking into account the complexity of construction tasks, allows to increase productivity, coordination and provide implementation of construction projects according to technical requirements.Discussion and conclusion. The results of the study prove that improving the organization structure and staff composition of construction companies in terms of costs is an important factor in the successful implementation of construction projects. Optimization of these elements leads to reducing costs, meeting deadlines for work and increasing the reliability of construction processes. Prospects for further research include improving methods for assessing the effectiveness of various construction departments and integrating innovative technologies into construction organization processes.